THE IMPACT OF THE GLOBAL FINANCIAL CRISIS ON THE EFFICIENCY OF FOREIGN BANKS IN TURKEY - (:unkn) unknown (SILESIAN UNIV, 2010)
The study empirically searches for the impact of the global financial crisis on the technical efficiency of foreign banks in Turkey. To estimate stochastic frontiers and to predict bank-level technical efficiencies relative to the estimated frontier, a Cobb-Douglas Stochastic Frontier Production Function is used for the period of 2002-2008. The study also estimates the bank specific determinants of technical inefficiencies of commercial banks in Turkey using a single equation of the Frontier model proposed by Battese and Coelli (1995). The results of the empirical research suggest that the ranking of commercial banks in terms of technical efficiency as state-owned, private domestic and foreign did not change during the crisis. The technical efficiencies of foreign bank subsidiaries, despite a decrease in 2007, are even closing the gap with private domestic commercial banks. The technical efficiency of state-owned banks, in contrast to both domestic and foreign private banks, continued to increase during both 2007 and 2008. The foreign bank subsidiaries have much higher technical efficiency scores compared to foreign bank branches, which have the most volatile efficiency scores. The technical efficiencies of commercial banks have a high, positive and statistically significant relation with the asset size.
Keywords: bank efficiency; restructuring and M&A; Stochastic Frontier Approach; financial crisis; PERFORMANCE; OWNERSHIP